Scottish cinema : texts and contexts - Meir, Christopher (Manchester University Press, 2015)
Beginning in the early 1980s and continuing today, Scottish cinema has over the last three decades seen an unprecedented number of international successes. Films ranging from Local Hero to The Last King of Scotland have not only raised the profile of film-making north of Hadrian's Wall, but have also raised a number of questions about the place of cinema originating from a small, historically marginalized, as yet stateless nation, within national and transnational film cultures. By providing detailed case studies of some of the biggest films of contemporary Scottish cinema, including Local Hero, Mrs. Brown, Morvern Callar and others, this volume will help readers to understand the key works of period as well as the interrelated industrial, critical and cultural contexts surrounding their creation and reception. As the field of Scottish film studies has also grown and developed during this period, this volume will also introduce readers to the debates sparked by the key works discussed in the book. By taking an approach that is rooted in detailed studies of individual films, yet providing the scope to understand a larger national cinema and the debates surrounding that cinema, Scottish Cinema: Texts and Contexts is an ideal volume for students new to Scottish cinema as well as scholars working in the field. This volume is also a must have for those interested in British cinema, European cinemas and concepts of national and transnational cinemas generally. --